Modulation and Demodulation of Image Processing by Using GMSK - R. Udawant, Sandip; Magar, Satyawati (International Journal of Engineering and Technology, 2018)
Today digital communication is widely used in telecommunication sector in which the information is coded in the form of bits. There are many techniques that are implemented for modulation in digital communication some of them are BPSK, QPSK, M-ary PSK, GMSK. While transmitting an image there is always a challenge to retain the quality of an image by using these digital modulation techniques. In this paper GMSK technique is used for transmitting an image. The GMSK modulation technique is widely used in GSM techniques. By using GMSK modulation technique, which carries the information with high data rate and this is very important for image transmission. The proposed system gives better results than other modulation techniques like BPSK and M-ary PSK.Â Â